1998
DOI: 10.1016/s0044-8486(98)00380-9
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of susceptibility to Vibrio penaeicida in Penaeus stylirostris postlarvae and juveniles

Abstract: Vibriosis is a major disease problem in shrimp aquaculture, affecting all developmental stages, from larvae in hatchery tanks to juveniles and broodstock in growout ponds. However, bacterial strains responsible for vibriosis in the successive stages are usually considered to be different, and virulence specificity has been reported both at the species and at the stage levels. The so-called « Syndrome 93 » is a seasonal juvenile vibriosis caused by Vibrio penaeicida which affects Penaeus stylirostris in growout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…However, most Vibrio species are now widely accepted as being opportunistic and may cause severe mortalities in larvae or juveniles, which suffer from stress or any deficiency. V. penaeicida disease is unique since this bacteria has been shown to be predominantly pathogenic for juvenile and adult shrimps, whereas post-larvae stages remain unaffected [16,27]. Indeed, vibrioses are mainly known to affect shrimp larvae and post-larvae.…”
Section: Discussionmentioning
confidence: 99%
“…However, most Vibrio species are now widely accepted as being opportunistic and may cause severe mortalities in larvae or juveniles, which suffer from stress or any deficiency. V. penaeicida disease is unique since this bacteria has been shown to be predominantly pathogenic for juvenile and adult shrimps, whereas post-larvae stages remain unaffected [16,27]. Indeed, vibrioses are mainly known to affect shrimp larvae and post-larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was tabulated after 7 d. These preliminary experiments showed that the following dosages resulted in killing approximately half of the population in 7 d: injections of 10 4 and 10 6 CFU V. parahaemolyticus and V. harveyi, respectively, and immersion in ASW containing 10 5 CFU ml -1 of either species. These dosages were selected for use in the present study and are also similar to published lethal dose (LD 50 ) values on shrimp, although different species, different lengths of exposure, and different stages in shrimp life cycles were used (see Arume 1989, Chen et al 1992, Jiravanichpaisal & Miyazaki 1994, Hameed 1995, Lee et al 1996, Goarant et al 1998, Vandenberghe et al 1999, Mikulski et al 2000.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental infections of aquatic animals using viruses, bacteria or parasites can be performed to fulfil different objectives: to estimate the efficiency of preventive treatments, study routes of infection, test the resistance of selected lines (Gomez-Leon et al, 2008;Goyard et al, 2008;Lallias et al, 2008) or different ploidy groups (Ching et al, 2009;O'Flynn et al, 1997), and to assess host factors linked to susceptibility (Goarant et al, 1998(Goarant et al, , 2006bLabreuche et al, 2006a). For bacteria, experimental infections are also often used to explore pathogenicity (Gay et al, 2004;Goarant et al, 2006b), coupled with phenotypic and/or molecular characterization of virulence factors.…”
Section: Potential and Limitations Of Bath Challenges Vs Injectionmentioning
confidence: 99%